Oxidation mechanism of refractory high entropy alloys Ta-Mo-Cr-Ti-Al with varying Ta content. (November 2021) - Schellert, S.; Gorr, B.; Laube, S.; Kauffmann, A.; Heilmaier, M.; Christ, H.J.
Abstract: The effect of Ta on the oxidation resistance of the alloys Tax -(Mo-Cr-Ti-Al)1−x (x=0; 5; 10; 15; 20 at%) in air at 1200 °C was examined. The oxidation behavior improves continuously with the increasing Ta concentration. Alloys with Ta concentrations Ta≤10 at% exhibit poor oxidation. Severe evaporation of MoO3 occurred which was quantitatively estimated. The evaporation of MoO3 is drastically reduced in alloys with the higher Ta concentrations. At 15 and 20 at% Ta, protective CrTaO4 scales are found. The CrTaO4 scale formed on Ta20 -(Mo-Cr-Ti-Al)80 grows according to the parabolic rate law as a result of oxygen inward diffusion. Highlights: The oxidation behavior improves continuously with the increasing Ta concentration. The evaporation of MoO3 was quantitatively estimated. The evaporation of MoO3 is drastically reduced in alloys with the higher Ta concentrations. The CrTaO4 scale formed on Ta20 -(Mo-Cr-Ti-Al)80 grows according to the parabolic rate law due to oxygen inward diffusion.